Essays in jurisprudence and philosophy - Hart, H. L. A. (Herbert Lionel Adolphus), 1907-1992. (Oxford : Clarendon, 1983)
These essays, which cover a wide range of topics, were written by Professor Hart between 1953 and 1981, and first appeared in a variety of different books and journals.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Jurisprudence; Law -- Philosophy